Geological heritage environmental situation in Peru - Rivas, Francisco (2001)
Current company led by developed countries shows an increasing sensitivity to the conservation and use of its assets , be it Natural or Historic- Cultural . Conservation trends today are clear and definite in regard to natural , such as flora, fauna and landscape to some extent , many areas in which social sectors are particularly active resources . However, the same with which in many countries has been recognized as part of the Natural Heritage is not the case , called the geological heritage and in which our country is privileged , for visible signs, often spectacular geology in different aspects geomorphological , structural, stratigraphic , petrological , mineralogical , mineral or paleontological sites , which are distributed throughout the country and on which there is no knowledge , protection, conservation and use of them, which may ultimately generate sustainable development in their environment.